Management of a Hypomineralisation of the Enamel by Applying a Remineraliser Based on Zinc Hydroxyapatite (microRepair) - G. Solinas; V. Grabesu; M. Lattari; R. Strinna; N. Arnould; A. A. Amodeo (Case Reports in Dentistry)
According to our experience, the treatment with remineralising mousse based on biomimetic nanohydroxyapatite has the advantage of being easily implemented by all patients as it is economical and absolutely noninvasive. The following case report reports the results obtained from the use of a mousse based on biomimetic nanohydroxyapatite for the treatment of incisor and molar hypomineralisation. This case report illustrates the case of a 4-year-old patient who was diagnosed with MIH and was subjected to remineralising treatments at home for six months, at alternating periods. Throughout the observation period, the painful perception of the lesions was detected through an assessment scale, and the clinical appearance was documented photographically. One year after the diagnosis, all the elements involved no longer showed any symptoms.